Binder composition for all-solid-state secondary batteries, slurry composition for all-solid-state secondary batteries, solid electrolyte-containing layer, and all-solid-state secondary batteries

KR103013400B1Active Publication Date: 2026-09-01ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020227012386
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-31
Filing Date
2020-10-14
Publication Date
2026-09-01
Estimated Expiration
2040-10-14

Smart Images

  • Figure 112022039612818-PCT00001
    Figure 112022039612818-PCT00001
  • Figure 112022039612818-PCT00002
    Figure 112022039612818-PCT00002
  • Figure 112022039612818-PCT00003
    Figure 112022039612818-PCT00003
Patent Text Reader

Abstract

The present invention aims to provide a binder composition for an all-solid-state secondary battery that can prepare a slurry composition for an all-solid-state secondary battery having excellent dispersibility and storage stability, while simultaneously exhibiting excellent ion conductivity in a solid electrolyte-containing layer. The binder composition of the present invention comprises a polymer, ions of a metal belonging to Group 1 or Group 2 of the periodic table, and a solvent. The solvent comprises an organic solvent having 8 or more carbon atoms, and the content of the metal ions is 5 mass ppm or more and 5,000 mass ppm or less relative to the polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a binder composition for an all-solid-state secondary battery, a slurry composition for an all-solid-state secondary battery, a solid electrolyte-containing layer, and an all-solid-state secondary battery. Background Technology

[0002] In recent years, the demand for secondary batteries, such as lithium-ion batteries, has been increasing in various applications, including small home power storage devices, motorcycles, electric vehicles, and hybrid electric vehicles, in addition to portable terminals such as portable information terminals and portable electronic devices. Furthermore, with the expansion of applications, there is a growing requirement for secondary batteries to further enhance safety.

[0003] Accordingly, all-solid-state secondary batteries using solid electrolytes are attracting attention as a safer secondary battery, replacing organic solvent electrolytes which are highly flammable and pose a high risk of ignition in the event of leakage. The solid electrolyte is contained within the all-solid-state secondary battery as a solid electrolyte-containing layer (electrode composite layer, solid electrolyte layer) formed by binding components, such as the solid electrolyte, together, for example, by a binder.

[0004] Here, for the formation of the solid electrolyte-containing layer, a slurry composition for the solid electrolyte-containing layer is used, which is prepared using a binder composition comprising a polymer as a binder and a solvent.

[0005] For example, an electrode composite layer can be formed by removing a solvent from a slurry composition for an electrode composite layer containing a binder composition, a solid electrolyte, and an electrode active material. Additionally, for example, a solid electrolyte layer can be formed by removing a solvent from a slurry composition for a solid electrolyte layer containing a binder composition and a solid electrolyte.

[0006] In addition, improvements to binder compositions and methods for forming a solid electrolyte-containing layer using binder compositions have been conventionally made to improve the performance of all-solid-state secondary batteries (see, for example, Patent Documents 1 and 2). Prior art literature

[0007] Japanese Published Patent Application No. 2010-205449 Japanese Published Patent Application No. 2019-91632 The problem to be solved

[0008] However, the above-mentioned conventional binder composition had room for improvement in terms of increasing the dispersibility and storage stability of the slurry composition, while simultaneously increasing the ionic conductivity of the solid electrolyte-containing layer formed using the slurry composition.

[0009] Accordingly, the present invention aims to provide a binder composition for an all-solid-state secondary battery that can prepare a slurry composition for an all-solid-state secondary battery having excellent dispersibility and storage stability, while simultaneously exhibiting excellent ion conductivity in a solid electrolyte-containing layer.

[0010] In addition, the present invention aims to provide a slurry composition for an all-solid-state secondary battery capable of forming a solid electrolyte-containing layer with excellent dispersibility and storage stability, while simultaneously having excellent ion conductivity.

[0011] In addition, the present invention aims to provide a solid electrolyte-containing layer having excellent ion conductivity and an all-solid-state secondary battery having said solid electrolyte-containing layer. means of solving the problem

[0012] The inventors of the present invention conducted a thorough examination with the aim of solving the above problem. The inventors newly discovered that by using a binder composition comprising a polymer, a predetermined metal ion, and a predetermined organic solvent, wherein the content of the metal ion relative to the polymer is within a predetermined range, excellent ion conductivity can be exhibited in a solid electrolyte-containing layer while sufficiently ensuring the dispersibility and storage stability of the slurry composition, and thus completed the present invention.

[0013] That is, the present invention aims to advantageously solve the above problem. The binder composition for an all-solid-state secondary battery according to the present invention comprises a polymer, ions of a metal belonging to Group 1 or Group 2 of the periodic table, and a solvent. The solvent comprises an organic solvent having 8 or more carbon atoms, and the content of the metal ions is 5 mass ppm or more and 5,000 mass ppm or less relative to the polymer. By using a binder composition comprising a polymer, ions of a metal belonging to Group 1 or Group 2 of the periodic table (hereinafter abbreviated as "metal ions of Group 1 or 2"), and a solvent, wherein the amount of metal ions of Group 1 or 2 relative to the polymer is within the range described above and the solvent comprises an organic solvent having 8 or more carbon atoms, a slurry composition having excellent dispersibility and storage stability can be prepared, and a solid electrolyte containing layer with excellent ion conductivity can be formed from the said secondary battery slurry composition.

[0014] Meanwhile, in the present invention, the content of metal ions belonging to Group 1 or Group 2 of the periodic table in the polymer can be measured by inductively coupled plasma emission spectroscopy (ICP-AES). Specifically, said content can be measured using the method described in the examples.

[0015] Here, in the binder composition for an all-solid-state secondary battery of the present invention, the organic solvent having 8 or more carbon atoms preferably has at least one selected from the group consisting of an aromatic hydrocarbon ring, a non-aromatic hydrocarbon group, and a carbonyl group. If the organic solvent having 8 or more carbon atoms has at least one of the structures described above, the ionic conductivity of the solid electrolyte-containing layer can be further increased while further improving the dispersibility and storage stability of the slurry composition.

[0016] In addition, in the binder composition for a solid-state secondary battery according to the present invention, it is preferable that the polymer has at least one of a nitrogen-containing functional group and a carbonyl group. If the polymer has at least one of the groups described above, the effect of further improving the dispersibility and storage stability of the slurry composition and / or improving the adhesion of the solid electrolyte-containing layer can be obtained.

[0017] In addition, in the binder composition for an all-solid-state secondary battery of the present invention, it is preferable that the polymer contains vinyl cyanide monomer units in a ratio of 2 mass% or more and 35 mass% or less. If the polymer contains vinyl cyanide monomer units in the ratio described above, the dispersibility and storage stability of the slurry composition can be further improved.

[0018] Meanwhile, in the present invention, "comprising monomer units" means that "structural units derived from monomers are included in the polymer obtained using the monomer." Furthermore, in the present invention, the content ratio (mass%) of the "structural units" (comprising "monomer units") in the polymer is, 1 It can be measured using nuclear magnetic resonance (NMR) methods such as H-NMR.

[0019] Here, in the binder composition for an all-solid-state secondary battery according to the present invention, it is preferable that the polymer contains (meth)acrylic acid ester monomer units not having aromatic hydrocarbon rings in a ratio of 25 mass% or more and 95 mass% or less. When the polymer contains (meth)acrylic acid ester monomer units not having aromatic hydrocarbon rings in the ratio described above, the dispersibility and storage stability of the slurry composition can be further improved, and the adhesion of the solid electrolyte-containing layer can be increased.

[0020] Meanwhile, in the present invention, "(meth)acrylic" means acrylic and / or methacrylic.

[0021] In addition, in the binder composition for an all-solid-state secondary battery according to the present invention, it is preferable that the polymer contains aromatic monomer units in a ratio of 3 mass% or more and 40 mass% or less. If the polymer contains aromatic monomer units in the ratio described above, the dispersibility and storage stability of the slurry composition can be further improved.

[0022] In addition, in the binder composition for an all-solid-state secondary battery according to the present invention, it is preferable that the aromatic monomer unit comprises a (meth)acrylic acid ester monomer unit having an aromatic hydrocarbon ring. If the polymer comprises a (meth)acrylic acid ester monomer unit having an aromatic hydrocarbon ring as the aromatic monomer unit, the adhesion of the solid electrolyte-containing layer can be improved.

[0023] In addition, the present invention aims to advantageously solve the above problem. The slurry composition for an all-solid-state secondary battery according to the present invention is characterized by comprising a solid electrolyte and any one of the all-solid-state secondary battery binder compositions described above. A slurry composition comprising a solid electrolyte and any one of the binder compositions described above has excellent dispersibility and storage stability, and furthermore, using the slurry composition can form a solid electrolyte-containing layer with excellent ion conductivity.

[0024] Here, in the slurry composition for an all-solid-state secondary battery of the present invention, it is preferable that the solid electrolyte comprises at least one of a sulfide-based inorganic solid electrolyte and an oxide-based inorganic solid electrolyte. If a sulfide-based inorganic solid electrolyte and / or an oxide-based inorganic solid electrolyte is used as the solid electrolyte, the ionic conductivity of the solid electrolyte-containing layer can be further improved.

[0025] In addition, the present invention aims to advantageously solve the above problem, and the solid electrolyte-containing layer of the present invention is characterized by being formed using any one of the slurry compositions for an all-solid-state secondary battery described above. The solid electrolyte-containing layer formed using any one of the slurry compositions described above has excellent ion conductivity.

[0026] Furthermore, the present invention aims to advantageously solve the above problem, and the all-solid-state secondary battery of the present invention is characterized by having the solid electrolyte-containing layer described above. The all-solid-state secondary battery having the solid electrolyte-containing layer described above has excellent cell characteristics, such as output characteristics and cycle characteristics. Effects of the invention

[0027] According to the present invention, it is possible to prepare a slurry composition for an all-solid-state secondary battery having excellent dispersibility and storage stability, and at the same time, provide a binder composition for an all-solid-state secondary battery that can exhibit excellent ion conductivity in a solid electrolyte-containing layer.

[0028] In addition, according to the present invention, a slurry composition for an all-solid-state secondary battery can be provided that is capable of forming a solid electrolyte-containing layer with excellent dispersibility and storage stability, while also having excellent ion conductivity.

[0029] In addition, according to the present invention, a solid electrolyte containing layer having excellent ion conductivity and an all-solid-state secondary battery having said solid electrolyte containing layer can be provided. Specific details for implementing the invention

[0030] Hereinafter, embodiments of the present invention will be described in detail.

[0031] The binder composition for an all-solid-state secondary battery of the present invention is used in the preparation of a slurry composition for an all-solid-state secondary battery. Here, the slurry composition for an all-solid-state secondary battery of the present invention is used when forming a solid electrolyte-containing layer, such as an electrode composite layer or a solid electrolyte layer, used in an all-solid-state secondary battery, such as an all-solid-state lithium-ion secondary battery. Furthermore, the solid electrolyte-containing layer of the present invention is formed using the slurry composition for an all-solid-state secondary battery of the present invention. Additionally, the all-solid-state secondary battery of the present invention comprises the solid electrolyte-containing layer of the present invention.

[0032] (Binder composition for all-solid-state secondary batteries)

[0033] The binder composition of the present invention comprises a polymer, metal ions of group 1 to 2, and a solvent, and may optionally further contain other components. Herein, the binder composition of the present invention is characterized in that the content of the metal ions of group 1 to 2 relative to the polymer is 5 mass ppm or more and 5,000 mass ppm or less, and the solvent comprises an organic solvent having 8 or more carbon atoms.

[0034] In addition, the binder composition of the present invention comprises a polymer, metal ions of group 1 to 2, and a solvent, wherein the ion content of the metal of group 1 to 2 is within the range described above and the solvent contains an organic solvent having 8 or more carbon atoms, so using the binder composition can provide a slurry composition for an all-solid-state secondary battery having excellent dispersibility and storage stability, and a solid electrolyte-containing layer having excellent ion conductivity.

[0035] Polymer

[0036] As for the polymer, any polymer can be used as long as it is a component capable of binding components such as the solid electrolyte together (i.e., a component capable of functioning as a binder) in a solid electrolyte-containing layer formed from a slurry composition prepared using a binder composition, without being particularly limited.

[0037] Composition

[0038] Here, it is preferable that the polymer comprises at least one of a nitrogen-containing functional group and a carbonyl group (-C(=O)-), and it is preferable that it comprises both a nitrogen-containing functional group and a carbonyl group. If the polymer has a nitrogen-containing functional group, the polymer is well adsorbed to the solid electrolyte, which can further improve the dispersibility and storage stability of the slurry composition. In addition, if the polymer has a carbonyl group, the flexibility of the polymer is ensured, which can improve the adhesion of the solid electrolyte-containing layer.

[0039] Meanwhile, nitrogen-containing functional groups include, for example, nitrile groups, amino groups, imidazole groups, pyridine groups, carbazole groups, and amide groups. In addition, the polymer may have one type of nitrogen-containing functional group or two or more types of nitrogen-containing functional groups.

[0040] In addition, the structural units contained in the polymer are not particularly limited. The polymer preferably comprises at least one selected from the group consisting of, for example, vinyl cyanide monomer units, (meth)acrylic acid ester monomer units not having an aromatic hydrocarbon ring, and aromatic monomer units. Meanwhile, the polymer may also comprise structural units other than vinyl cyanide monomer units, (meth)acrylic acid ester monomer units not having an aromatic hydrocarbon ring, and aromatic monomer units (other structural units).

[0041] [Vinyl cyanide monomer unit]

[0042] Examples of vinyl cyanide monomers capable of forming vinyl cyanide monomer units include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, and α-ethylacrylonitrile. One of these may be used alone, or two or more may be used in combination. Among these, acrylonitrile is preferred.

[0043] Here, among the total structural units included in the polymer, the proportion of vinyl cyanide monomer units is preferably 2 mass% or more, more preferably 3 mass% or more, even more preferably 4 mass% or more, particularly preferably 6 mass% or more, preferably 35 mass% or less, more preferably 28 mass% or less, even more preferably 26 mass% or less, and particularly preferably 20 mass% or less. If the proportion of vinyl cyanide monomer units in the total structural units is 2 mass% or more, the polymer is adsorbed well with the solid electrolyte, which can further improve the dispersibility and storage stability of the slurry composition. On the other hand, if the proportion of vinyl cyanide monomer units in the total structural units is 35 mass% or less, the polymer is dissolved well in the solvent (especially an organic solvent having 8 or more carbon atoms), which can further improve the dispersibility and storage stability of the slurry composition.

[0044] [(meth)acrylic acid ester monomer unit not having an aromatic hydrocarbon ring]

[0045] (Meth)acrylic acid ester monomers capable of forming (meth)acrylic acid ester monomer units not having an aromatic hydrocarbon ring are not particularly limited as long as they do not have an aromatic hydrocarbon ring. Examples of (meth)acrylic acid ester monomers not having an aromatic hydrocarbon ring include, for instance, alkyl acrylate methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, stearyl acrylate, 2-ethylhexyl acrylate; Acrylic acid alkoxyesters such as 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate; 2-(perfluoroalkyl)ethyl acrylates such as 2-(perfluorobutyl)ethyl acrylate, 2-(perfluoropentyl)ethyl acrylate; alkyl methacrylate esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, tridecyl methacrylate, n-tetradecyl methacrylate, stearyl methacrylate, 2-ethylhexyl methacrylate; Examples include methacrylic acid alkoxyesters such as 2-methoxyethyl methacrylate and 2-ethoxyethyl methacrylate; and 2-(perfluoroalkyl)ethyl methacrylates such as 2-(perfluorobutyl)ethyl methacrylate and 2-(perfluoropentyl)ethyl methacrylate. In addition, (meth)acrylic acid ester monomers include diesters of α,β-ethylenically unsaturated dicarboxylic acids, and lower alkyl diesters of itaconic acid such as diethyl itaconate and dibutyl itaconate.

[0046] These may be used individually or in combination of two or more types. Among these, methyl acrylate, ethyl acrylate, methyl methacrylate, butyl acrylate (n-butyl acrylate, t-butyl acrylate, etc.), and dibutyl itaconate are preferred.

[0047] Here, among the total structural units included in the polymer, the proportion of (meth)acrylic acid ester monomer units not having an aromatic hydrocarbon ring is preferably 25 mass% or more, more preferably 30 mass% or more, even more preferably 35 mass% or more, preferably 95 mass% or less, more preferably 90 mass% or less, even more preferably 85 mass% or less, and particularly preferably 73 mass% or less. If the proportion of (meth)acrylic acid ester monomer units not having an aromatic hydrocarbon ring in the total structural units is 25 mass% or more, the flexibility of the polymer is secured and the adhesion of the solid electrolyte-containing layer can be improved, and if it is 95 mass% or less, the polymer can be adsorbed well to the electrode active material or conductive material, thereby further improving the dispersibility and storage stability of the slurry composition.

[0048] [Aromatic monomer unit]

[0049] Aromatic monomers capable of forming aromatic monomer units are not particularly limited as long as they have an aromatic ring. Examples of aromatic monomers include aromatic vinyl monomers and (meth)acrylic acid ester monomers having an aromatic hydrocarbon ring.

[0050] Meanwhile, in the present invention, the aromatic vinyl monomer does not include a monomer corresponding to a (meth)acrylic acid ester monomer having an aromatic hydrocarbon ring (in other words, the aromatic vinyl monomer unit does not include a (meth)acrylic acid ester monomer unit having an aromatic hydrocarbon ring).

[0051] Here, aromatic vinyl monomers include, for example, styrene, styrenesulfonic acid and its salts, α-methylstyrene, pt-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene.

[0052] In addition, the aromatic hydrocarbon ring included in the (meth)acrylic acid ester monomer unit having an aromatic hydrocarbon ring is not particularly limited, but examples include a benzene ring, a naphthalene ring, and anthracene ring. Among these, a benzene ring is preferred. Meanwhile, the monomer unit may have one type of aromatic hydrocarbon ring or two or more types of aromatic hydrocarbon rings.

[0053] In addition, examples of (meth)acrylic acid ester monomers having an aromatic hydrocarbon ring include phenoxyethyl (meth)acrylate, phenyl (meth)acrylate, ethoxylated o-phenylphenol (meth)acrylate, and phenoxypolyethylene glycol (meth)acrylate.

[0054] Meanwhile, in the present invention, "(meth)acrylate" means acrylate and / or methacrylate.

[0055] The aforementioned aromatic monomers may be used as a single type or in combination of two or more types. Among these, styrene and phenoxyethyl acrylate are preferred from the perspective of adsorbing the polymer well with the solid electrolyte to further improve the dispersibility and storage stability of the slurry composition. Additionally, from the perspective of securing the flexibility of the polymer to improve the adhesion of the solid electrolyte-containing layer, (meth)acrylic acid ester monomers having an aromatic hydrocarbon ring are preferred, and phenoxyethyl acrylate is more preferred.

[0056] Here, among the total structural units included in the polymer, the proportion of aromatic monomer units is preferably 3 mass% or more, more preferably 5 mass% or more, even more preferably 7 mass% or more, particularly preferably 10 mass% or more, preferably 40 mass% or less, more preferably 35 mass% or less, even more preferably 30 mass% or less, and particularly preferably 25 mass% or less. If the proportion of aromatic monomer units in the total structural units is 3 mass% or more, the polymer can be adsorbed well with the solid electrolyte, thereby further improving the dispersibility and storage stability of the slurry composition. On the other hand, if the proportion of aromatic monomer units in the total structural units is 40 mass% or less, the polymer can be adsorbed well with the solid electrolyte, thereby further improving the dispersibility and storage stability of the slurry composition, while increasing the adhesion of the solid electrolyte-containing layer.

[0057] [Other structural units]

[0058] Other structural units are not particularly limited but may include diene monomer units and crosslinkable monomer units. Meanwhile, the polymer may contain only one type of other structural unit, or may contain two or more types of other structural units.

[0059] -Dienic monomer unit-

[0060] Examples of diene monomers capable of forming diene monomer units include aliphatic conjugated diene monomers such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. These may be used individually or in combination of two or more types.

[0061] Meanwhile, in the present invention, the "diene-based monomer unit" includes a monomer unit included in a polymer obtained using a diene-based monomer, and also includes a structural unit (hydride unit) obtained by hydrogenation.

[0062] And among the aforementioned diene monomers, 1,3-butadiene and isoprene are preferred. In other words, as diene monomer units, 1,3-butadiene units, isoprene units, 1,3-butadiene hydride units, and isoprene hydride units are preferred.

[0063] Here, when the polymer contains diene-based monomer units, the proportion of diene-based monomer units among the total structural units included in the polymer is preferably 5 mass% or more, more preferably 6 mass% or more, even more preferably 7 mass% or more, preferably 50 mass% or less, and more preferably 40 mass% or less, with the total structural units being 100 mass%. If the proportion of diene-based monomer units in the total structural units is 5 mass% or more, the polymer can be adsorbed well onto the electrode active material or conductive material, thereby further improving the dispersibility and storage stability of the slurry composition. On the other hand, if the proportion of diene-based monomer units in the total structural units is 50 mass% or less, sufficient adhesion of the solid electrolyte-containing layer can be ensured.

[0064] -Cross-linkable monomer unit-

[0065] A crosslinkable monomer capable of forming a crosslinkable monomer unit is a monomer having two or more polymerizable structures (olefinic double bonds, epoxy groups, etc.) per molecule. Examples of crosslinkable monomers include allyl (meth)acrylate, allylglycidyl ether, and ethylene glycol di(meth)acrylate. These may be used individually or in combination of two or more types.

[0066] Here, when the polymer contains crosslinkable monomer units, the proportion of crosslinkable monomer units among the total structural units included in the polymer can be 0.1 mass% or more with respect to 100 mass% of the total structural units, and is preferably 5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less.

[0067] <<Image>>

[0068] The polymer may be either soluble or insoluble with respect to the solvent included in the binder composition and the slurry composition. That is, the polymer may be in a dissolved state in the solvent within the binder composition and the slurry composition, or may be in a particulate state dispersed in the solvent.

[0069] Here, in the present invention, "soluble in a solvent" means that the amount of insoluble in the solvent is less than 50 mass%, and "poorly soluble in a solvent" means that the amount of insoluble in the solvent is 50 mass% or more.

[0070] Meanwhile, in the present invention, the "amount insoluble in the solvent" can be measured using the method described in the examples. Furthermore, the "amount insoluble in the solvent" of the polymer can be adjusted by changing the type of monomer used in preparing the polymer, the weight-average molecular weight of the polymer, etc. For example, the amount insoluble in the solvent can be reduced by reducing the amount of vinyl cyanide monomer and / or crosslinkable monomer used in preparing the polymer.

[0071] Here, it is preferable that the polymer be compatible with the solvent included in the binder composition and the slurry composition. If the polymer is compatible with the solvent, an even better dispersion state can be achieved in the slurry composition, such as a solid electrolyte, thereby further improving the dispersibility and storage stability of the slurry composition. Additionally, the adhesion of the solid electrolyte-containing layer can be increased.

[0072] <<Preparation Method>>

[0073] The method for preparing the polymer is not particularly limited, but, for example, the polymer can be prepared by polymerizing a monomer composition containing the monomer described above and optionally performing hydrogenation.

[0074] Here, in the present invention, the content ratio of each monomer in the monomer composition can be determined based on the content ratio of each monomer unit in the polymer.

[0075] The polymerization method may be any method such as solution polymerization, suspension polymerization, bulk polymerization, or emulsion polymerization, without any particular limitations. In each polymerization method, known emulsifiers or polymerization initiators may be used as needed. Here, as the emulsifier, nonionic emulsifiers such as polyoxyethylene lauryl ether may be used, but emulsifiers containing Group 1 or 2 metal ions such as sodium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sodium dodecyl diphenyl ether sulfonate, and sodium polyoxyethylene alkyl ether sulfate may also be used. By using an emulsifier containing Group 1 or 2 metal ions, Group 1 or 2 metal ions can be incorporated into the binder composition obtained.

[0076] The method of hydrogenation may use general methods using a catalyst without particular limitation (e.g., see International Publication No. 2012 / 165120, International Publication No. 2013 / 080989 and Japanese Patent Publication No. 2013-8485).

[0077] <Ions of metals belonging to Group 1 or Group 2 of the periodic table>

[0078] The binder composition of the present invention includes metal ions of Group 1 to 2. By including metal ions of Group 1 to 2 in the binder composition, the ionic conductivity of the solid electrolyte-containing layer can be improved. Although the reason for this is not clear, it is presumed that in the slurry composition and in the solid electrolyte-containing layer, metal ions of Group 1 to 2 are adsorbed onto the surface of the solid electrolyte through electrostatic interaction, etc., and thus coat the said surface, thereby suppressing the reaction occurring between water and the solid electrolyte, and thus suppressing the deterioration of the solid electrolyte caused by said reaction.

[0079] Here, as metal ions of groups 1 and 2, for example, sodium ions (Na + ), potassium ions (K + ), lithium ion (Li + ), magnesium ions (Mg 2+ ), calcium ions (Ca 2+ Examples include ). These may be used individually or in combination of two or more types. Among these, sodium ions and lithium ions are more preferable from the perspective of increasing the adhesion of the solid electrolyte-containing layer while further improving ion conductivity.

[0080] In addition, the content of metal ions of Group 1 to 2 in the binder composition needs to be 5 mass ppm or more and 5,000 mass ppm or less with respect to the polymer described above, preferably 10 mass ppm or more, more preferably 300 mass ppm or more, preferably 4,500 mass ppm or less, and more preferably 3,000 mass ppm or less. If the content of metal ions of Group 1 to 2 is less than 5 mass ppm with respect to the polymer, the effect of improving the ion conductivity of the solid electrolyte-containing layer described above cannot be sufficiently obtained, and if it exceeds 5,000 mass ppm, there is a risk that the metal ions will aggregate the solid electrolyte and polymer, etc., thereby impairing the dispersibility and storage stability of the slurry composition.

[0081] Meanwhile, the method of incorporating Group 1 and 2 metal ions into the binder composition is not particularly limited. For example, a binder composition containing Group 1 and 2 metal ions can be prepared by using an emulsifier containing the aforementioned Group 1 and 2 metal ions in the preparation of the polymer, or by adding a substance capable of supplying Group 1 and 2 metal ions (such as a Group 1 or 2 hydroxide) after the preparation of the polymer. In addition, for example, the amount of Group 1 and 2 metal ions contained in the binder composition obtained can be reduced by passing the polymer through an ion exchange resin.

[0082] <Solvent>

[0083] The binder composition of the present invention comprises an organic solvent having 8 or more carbon atoms as a solvent. It is inferred that by including an organic solvent having 8 or more carbon atoms in the binder composition, the aggregation of polymers and solid electrolytes, etc., in a slurry composition prepared using said binder composition is suppressed, thereby improving the dispersibility and storage stability of the slurry composition. Furthermore, an organic solvent having 8 or more carbon atoms is difficult to react with solid electrolytes and, additionally, has a high boiling point, so it has excellent handling properties. Therefore, by using an organic solvent having 8 or more carbon atoms as a solvent, solid electrolytes, etc., can be uniformly arranged to form a solid electrolyte-containing layer with excellent ion conductivity.

[0084] <<Organic solvents with 8 or more carbon atoms>>

[0085] Here, an organic solvent having 8 or more carbon atoms is preferably selected from the group consisting of aromatic hydrocarbon rings, non-aromatic hydrocarbon groups, and carbonyl groups, in order to further improve the dispersibility and storage stability of the slurry composition and further increase the ionic conductivity of the solid electrolyte-containing layer.

[0086] Examples of aromatic hydrocarbon rings include benzene rings, naphthalene rings, and anthracene rings. Meanwhile, organic solvents having 8 or more carbon atoms may contain only one type of aromatic hydrocarbon ring or two or more types.

[0087] Examples of non-aromatic hydrocarbon groups include alkyl groups such as methyl groups, propyl groups (n-propyl groups, isopropyl groups), and butyl groups (n-butyl groups, sec-butyl groups, isobutyl groups, tert-butyl groups). Meanwhile, organic solvents having 8 or more carbon atoms may contain only one type of non-aromatic hydrocarbon group or may contain two or more types.

[0088] In addition, the number of carbon atoms of the organic solvent in question needs to be 8 or more as described above, and from the perspective of further improving the dispersibility and storage stability of the slurry composition and further increasing the ionic conductivity of the solid electrolyte-containing layer, it is preferable that it be 12 or less, more preferable that it be 10 or less, and most preferable that it be 9.

[0089] Here, specific organic solvents having 8 or more carbon atoms include xylene (8 carbon atoms), butyl butyrate (8 carbon atoms), n-butyl ether (8 carbon atoms), diisobutyl ketone (9 carbon atoms), and hexyl butyrate (10 carbon atoms). These may be used individually or in combination of two or more types. Among these, diisobutyl ketone is preferred in terms of further improving the dispersibility of the slurry composition and the ionic conductivity of the solid electrolyte-containing layer.

[0090] Other Solvents

[0091] Meanwhile, the binder composition of the present invention may contain, as a solvent, a solvent other than the organic solvent having 8 or more carbon atoms described above (other solvent). As such other solvent, an organic solvent having 7 or fewer carbon atoms may be used. Specific organic solvents having 7 or fewer carbon atoms include hexane, cyclopentane, cyclohexane, ethylmethyl ketone, cyclohexanone, ethyl acetate, butyl acetate, γ-butyrolactone, ε-caprolactone, acetonitrile, propionitrile, tetrahydrofuran, methanol, ethanol, isopropanol, ethylene glycol, ethylene glycol monomethyl ether, N-methylpyrrolidone, N,N-dimethylformamide, etc. These may be used individually or in combination of two or more types.

[0092] However, from the perspective of sufficiently increasing the dispersibility and storage stability of the slurry composition and the ionic conductivity of the solid electrolyte-containing layer, the proportion of an organic solvent having 8 or more carbon atoms in the solvent is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, particularly preferably 95 mass% or more, and most preferably 100 mass% (i.e., not substantially containing other solvents).

[0093] Other ingredients

[0094] Other components that may optionally be contained in the binder composition are not particularly limited, but may include binders, dispersants, leveling agents, defoaming agents, conductive materials, and reinforcing materials other than the polymer described above. These other components are not particularly limited as long as they do not affect the battery reaction.

[0095] In addition, the binder composition may include a metal component (another metal component) other than the metal ions of Group 1 or 2 described above as other components.

[0096] Other metallic components include metals belonging to the fifth period of the periodic table (palladium, ruthenium, rhodium, etc.). Other metallic components may be used as a single type or in combination of two or more types.

[0097] In addition, when the binder composition includes at least one of palladium, ruthenium, and rhodium, it is preferable that the total amount thereof is 0.5 mass ppm or more and 200 mass ppm or less with respect to the polymer. If the total amount of palladium, ruthenium, and rhodium is within the above-described range, the electronic conductivity of the all-solid-state secondary battery is improved, and the output characteristics are improved. Furthermore, if the total amount of palladium, ruthenium, and rhodium is 200 mass ppm or less, the cycle characteristics of the all-solid-state secondary battery can be sufficiently improved.

[0098] Here, palladium, ruthenium, and rhodium may each be included in the binder composition by originating from compounds such as catalysts used in the preparation of polymers. Additionally, palladium, ruthenium, and rhodium may also be included in the binder composition by adding palladium-based compounds such as organic complexes and organic salts of palladium, ruthenium-based compounds such as organic complexes and organic salts of ruthenium, and rhodium-based compounds such as organic complexes and organic salts of rhodium to the binder composition.

[0099] Meanwhile, the other ingredients mentioned above may be used as a single type, or two or more types may be combined in any ratio.

[0100] In addition, in the present invention, the content of the other metal component described above can be measured by inductively coupled plasma emission spectroscopy (ICP-AES). Specifically, the said content can be measured using the method described in the examples.

[0101] Method for preparing a binder composition

[0102] The method for preparing the binder composition of the present invention is not particularly limited. For example, a binder composition can be prepared by adding a substance capable of supplying metal ions of Group 1 or 2 as needed to an aqueous dispersion of a polymer used as a binder obtained as described above, and then performing solvent substitution with an organic solvent having 8 or more carbon atoms. Meanwhile, as needed, other components may be added, for example, after solvent substitution.

[0103] (Slurry composition for all-solid-state secondary batteries)

[0104] The slurry composition for an all-solid-state secondary battery according to the present invention comprises at least a solid electrolyte and the binder composition for an all-solid-state secondary battery according to the present invention described above. More specifically, the slurry composition according to the present invention comprises a solid electrolyte, a solvent containing the polymer described above and metal ions of Group 1 or 2, and an organic solvent having 8 or more carbon atoms, and optionally, an electrode active material and other components. Furthermore, since the slurry composition according to the present invention includes the binder composition according to the present invention, it has excellent dispersibility and storage stability, and using the slurry composition allows for the formation of a solid electrolyte-containing layer with excellent ion conductivity.

[0105] Solid Electrolyte

[0106] As for the solid electrolyte, it is not particularly limited as long as it consists of particles made of a solid having ion conductivity, but an inorganic solid electrolyte can be preferably used.

[0107] As for the inorganic solid electrolyte, crystalline inorganic ion conductors, amorphous inorganic ion conductors, or mixtures thereof may be used, without being particularly limited. Furthermore, for example, when the all-solid-state secondary battery is an all-solid-state lithium-ion secondary battery, the inorganic solid electrolyte may typically be a crystalline inorganic lithium-ion conductor, an amorphous inorganic lithium-ion conductor, or a mixture thereof. Among these, from the perspective of forming a solid electrolyte-containing layer with even better ion conductivity, it is preferable that the inorganic solid electrolyte comprises at least one of a sulfide-based inorganic solid electrolyte and an oxide-based inorganic solid electrolyte.

[0108] Meanwhile, below, as an example, a case is described in which the slurry composition for an all-solid-state secondary battery is a slurry composition for an all-solid-state lithium-ion secondary battery, but the present invention is not limited to the following example.

[0109] And, as crystalline inorganic lithium ion conductors, Li3N, LISICON(Li14 Zn(GeO4)4), perovskite type (e.g., Li 0.5 La 0.5 TiO3), garnet type (e.g., Li7La3Zr2O 12 ), LIPON(Li 3+y PO 4-x N x ), Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S4) etc. can be cited.

[0110] The crystalline inorganic lithium ion conductor described above can be used alone or in a mixture of two or more types.

[0111] In addition, amorphous inorganic lithium ion conductors may include, for example, materials containing sulfur atoms and also having ion conductivity, and more specifically, materials made using a raw material composition containing glass Li-Si-SO, Li-PS, and Li2S and sulfides of elements of Groups 13 to 15 of the periodic table.

[0112] Here, examples of elements of Groups 13 to 15 include Al, Si, Ge, P, As, Sb, etc. Additionally, examples of sulfides of elements of Groups 13 to 15 include Al2S3, SiS2, GeS2, P2S3, P2S5, As2S3, Sb2S3, etc. Furthermore, methods for synthesizing amorphous inorganic lithium-ion conductors using the raw material composition include, for example, amorphization methods such as mechanical milling or melt quenching. Moreover, among the amorphous inorganic lithium-ion conductors formed using a raw material composition containing Li2S and sulfides of elements of Groups 13 to 15 of the periodic table, Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, or Li2S-Al2S3 are preferred, and Li2S-P2S5 is more preferred.

[0113] The above-described amorphous inorganic lithium ion conductor can be used alone or in a mixture of two or more types.

[0114] Among the above, as an inorganic solid electrolyte for an all-solid-state lithium-ion secondary battery, in terms of forming a solid electrolyte-containing layer with even better ion conductivity, an amorphous sulfide containing Li and P, Li7La3Zr2O 12 It is preferable. Amorphous sulfides containing Li and P, and Li7La3Zr2O 12 Since it has high lithium ion conductivity, it can be used as an inorganic solid electrolyte to lower the internal resistance of the battery and improve output characteristics.

[0115] Meanwhile, regarding the reduction of internal resistance and improvement of output characteristics of the battery, it is more preferable for the amorphous sulfide containing Li and P to be a sulfide glass composed of Li2S and P2S5, and particularly preferable for it to be a sulfide glass prepared from a mixed raw material of Li2S and P2S5 with a molar ratio of Li2S:P2S5 of 65:35 to 85:15. In addition, regarding the amorphous sulfide containing Li and P, it is preferable for it to be a sulfide glass ceramic obtained by reacting a mixed raw material of Li2S and P2S5 with a molar ratio of Li2S:P2S5 of 65:35 to 85:15 by a mechanochemical method. Meanwhile, regarding maintaining high lithium ion conductivity, it is preferable for the mixed raw material to have a molar ratio of Li2S:P2S5 of 68:32 to 80:20.

[0116] Meanwhile, the inorganic solid electrolyte may include at least one sulfide selected from the group consisting of Al2S3, B2S3, and SiS2 as a starting material in addition to the above Li2S and P2S5, to the extent that it does not reduce ion conductivity. Adding such a sulfide can stabilize the glass components in the inorganic solid electrolyte.

[0117] Likewise, in addition to Li2S and P2S5, the inorganic solid electrolyte may contain at least one lithium orthooxate selected from the group consisting of Li3PO4, Li4SiO4, Li4GeO4, Li3BO3, and Li3AlO3. Including such lithium orthooxate can stabilize the free components in the inorganic solid electrolyte.

[0118] Meanwhile, the solid electrolyte described above can be used alone or in a mixture of two or more types. In addition, the particle size of the solid electrolyte described above is not particularly limited and can be the same as that of conventionally used solid electrolytes.

[0119] <Binder Composition>

[0120] As a binder composition used in the preparation of a slurry composition, the binder composition of the present invention described above is used, which comprises a polymer, a metal ion of group 1 or 2, and a solvent containing an organic solvent having 8 or more carbon atoms, and optionally contains other components.

[0121] Meanwhile, the ratio of the solid electrolyte to the binder composition is not particularly limited.

[0122] For example, the amount of polymer derived from the binder composition included in the slurry composition is preferably 0.1 parts by mass or more per 100 parts by mass of solid electrolyte, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less. If the content of the polymer in the slurry composition is 0.1 parts by mass or more per 100 parts by mass of solid electrolyte, the polymer can sufficiently perform its function as a binder, and the dispersibility and storage stability of the slurry composition can be further enhanced. In addition, the ion conductivity of the solid electrolyte-containing layer can be further improved, thereby enhancing the cell characteristics of the all-solid-state battery. Meanwhile, if the content of the polymer in the slurry composition is 10 parts by mass or less per 100 parts by mass of solid electrolyte, sufficient ion conductivity of the solid electrolyte-containing layer can be secured, and the cell characteristics of the all-solid-state secondary battery are not excessively damaged.

[0123] Electrode active material

[0124] The electrode active material is a substance that exchanges electrons at the electrode of an all-solid-state secondary battery. And, for example, when the all-solid-state secondary battery is an all-solid-state lithium-ion secondary battery, a material capable of absorbing and releasing lithium is typically used as the electrode active material.

[0125] Meanwhile, below, as an example, a case is described in which the slurry composition for an all-solid-state secondary battery is a slurry composition for an all-solid-state lithium-ion secondary battery, but the present invention is not limited to the following example.

[0126] In addition, positive electrode active materials for all-solid-state lithium-ion secondary batteries are not particularly limited and may include positive electrode active materials composed of inorganic compounds and positive electrode active materials composed of organic compounds. Meanwhile, the positive electrode active material may be a mixture of inorganic compounds and organic compounds.

[0127] Examples of positive electrode active materials composed of inorganic compounds include transition metal oxides, complex oxides of lithium and transition metals (lithium-containing complex metal oxides), and transition metal sulfides. The above transition metals used include Fe, Co, Ni, Mn, etc. Specific examples of inorganic compounds used as positive electrode active materials include lithium-containing complex metal oxides such as LiCoO2 (lithium cobaltate), LiNiO2, LiMnO2, LiMn2O4, LiFePO4, and LiFeVO4; transition metal sulfides such as TiS2, TiS3, and amorphous MoS2; and Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, and V6O. 13 Examples include transition metal oxides such as the above. These compounds may be partially elementally substituted.

[0128] The positive electrode active material composed of the inorganic compound described above can be used alone or in a mixture of two or more types.

[0129] Examples of positive electrode active materials composed of organic compounds include polyaniline, polypyrrole, polyacene, disulfide compounds, polysulfide compounds, N-fluoropyridinium salts, etc.

[0130] The positive electrode active material composed of the organic compounds described above can be used alone or in a mixture of two or more types.

[0131] In addition, allotropes of carbon such as graphite or coke can be used as negative electrode active materials for all-solid-state lithium-ion secondary batteries. Meanwhile, negative electrode active materials composed of allotropes of carbon may also be used in the form of a mixture or coating with metals, metal salts, oxides, etc. In addition, oxides or sulfates of silicon, tin, zinc, manganese, iron, nickel, etc.; metallic lithium; lithium alloys such as Li-Al, Li-Bi-Cd, Li-Sn-Cd; lithium transition metal nitrides; silicon; etc. can also be used as negative electrode active materials.

[0132] The aforementioned negative electrode active material can be used alone or in a mixture of two or more types.

[0133] Meanwhile, the particle size of the electrode active material (positive electrode active material, negative electrode active material) described above is not particularly limited and can be the same as that of the electrode active material used in the past. In addition, the amount of the electrode active material described above in the slurry composition is not particularly limited and can be the same as that of the electrode active material used in the past.

[0134] <Preparation of Slurry Composition>

[0135] In addition, the above-described slurry composition for a solid-state secondary battery is not particularly limited and can be obtained by mixing the above-described components using, for example, any mixing method.

[0136] (Solid electrolyte-containing layer)

[0137] The solid electrolyte-containing layer of the present invention is a layer containing a solid electrolyte, and the solid electrolyte-containing layer may include, for example, an electrode composite layer (positive electrode composite layer, negative electrode composite layer) that performs the transfer of electrons through an electrochemical reaction, or a solid electrolyte layer formed between a positive electrode composite layer and a negative electrode composite layer facing each other.

[0138] Furthermore, the solid electrolyte-containing layer of the present invention is formed using the above-described slurry composition for an all-solid-state secondary battery, for example, by applying the above-described slurry composition to the surface of a suitable substrate to form a coating film, and then drying the formed coating film. That is, the solid electrolyte-containing layer of the present invention is composed of a dried product of the above-described slurry composition and typically comprises a solid electrolyte, a polymer, and ions of a metal belonging to Group 1 or Group 2 of the periodic table (and / or an ionic compound composed of said metal ions (cations) and anions), and optionally may further contain at least one selected from the group consisting of an electrode active material and other components. Meanwhile, each component contained in the solid electrolyte-containing layer is one that was contained in the above-described slurry composition, and the content ratio of such components is typically equivalent to the content ratio in the above-described slurry composition.

[0139] In addition, since the solid electrolyte-containing layer of the present invention is formed from the slurry composition for an all-solid-state secondary battery of the present invention, it can exhibit excellent ion conductivity.

[0140] <Information>

[0141] Here, there are no restrictions on the substrate to which the slurry composition is applied. For example, a film of the slurry composition may be formed on the surface of a release substrate, the film may be dried to form a solid electrolyte-containing layer, and the release substrate may be detached from the solid electrolyte-containing layer. In this way, the solid electrolyte-containing layer detached from the release substrate may be used as a self-supporting film to form a battery component of an all-solid-state secondary battery (e.g., an electrode or a solid electrolyte layer).

[0142] However, from the perspective of increasing the manufacturing efficiency of battery components by omitting the process of removing the solid electrolyte-containing layer, it is preferable to use a current collector or an electrode as the substrate. Specifically, when preparing the electrode composite layer, it is preferable to apply the slurry composition onto the current collector as the substrate. In addition, when preparing the solid electrolyte layer, it is preferable to apply the slurry composition onto the electrode (positive electrode or negative electrode).

[0143] <<Whole House>>

[0144] As a current collector, a material that is electrically conductive and also electrochemically durable is used. Specifically, as a current collector, for example, a current collector made of iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc., can be used. Among these, copper foil is particularly preferred as a current collector used for the negative electrode. Also, aluminum foil is particularly preferred as a current collector used for the positive electrode. Meanwhile, the above materials may be used as a single type or two or more types may be used in combination in any ratio.

[0145] <<Electrode>>

[0146] As for the electrodes (positive and negative electrodes), although not particularly limited, an electrode may be provided in which an electrode composite layer comprising an electrode active material, a solid electrolyte, and a binder is formed on the current collector described above.

[0147] The electrode active material, solid electrolyte, and binder included in the electrode composite layer within the electrode are not particularly limited and known materials may be used. Meanwhile, the electrode composite layer within the electrode may correspond to the solid electrolyte-containing layer of the present invention.

[0148] Method for forming a solid electrolyte-containing layer

[0149] The following methods may be used to form a solid electrolyte-containing layer on a substrate such as a current collector or electrode as described above.

[0150] 1) A method of applying the slurry composition of the present invention to the surface of a substrate (in the case of an electrode, the surface on the electrode composite layer side, hereinafter the same) and then drying;

[0151] 2) A method of immersing a substrate in the slurry composition of the present invention and then drying it; and

[0152] 3) A method of applying the slurry composition of the present invention onto a release substrate, drying to produce a solid electrolyte-containing layer, and transferring the obtained solid electrolyte-containing layer to the surface of an electrode, etc.

[0153] Among these, the method of 1) above is particularly preferred in that it is easy to control the thickness of the solid electrolyte-containing layer. Specifically, the method of 1) includes a process of applying a slurry composition onto a substrate (coating process) and a process of drying the slurry composition applied onto the substrate to form a solid electrolyte-containing layer (solid electrolyte-containing layer formation process).

[0154] Coating Process

[0155] In addition, regarding the coating process, there are no particular limitations on the method of applying the slurry composition onto the substrate, and examples include the doctor blade method, reverse roll method, direct roll method, gravure method, extrusion method, brush coating method, etc.

[0156] <<Solid Electrolyte-Containing Layer Formation Process>>

[0157] In addition, in the process of forming a solid electrolyte-containing layer, the method of drying the slurry composition on the substrate is not particularly limited and known methods may be used. Examples of drying methods include drying by hot air, hot air, low humidity air, vacuum drying, and drying by irradiation with infrared rays or electron beams.

[0158] Meanwhile, when the solid electrolyte-containing layer is an electrode composite layer, it is preferable to perform a press treatment using a roll press or the like after drying. By performing the press treatment, the resulting electrode composite layer can be made even more dense.

[0159] (electrode)

[0160] In addition, an electrode formed by forming an electrode composite layer on a current collector using the slurry composition for an all-solid-state secondary battery of the present invention comprises a solid electrolyte, a polymer, and an ion of a metal belonging to Group 1 or Group 2 of the periodic table (and / or an ionic compound consisting of an ion (cation) of said metal and an anion), and optionally further comprises at least one selected from the group consisting of an electrode active material and other components, thereby exhibiting excellent ion conductivity.

[0161] (Solid electrolyte layer)

[0162] In addition, the solid electrolyte layer formed using the all-solid-state secondary battery slurry composition of the present invention comprises a solid electrolyte, a polymer, and ions of a metal belonging to Group 1 or Group 2 of the periodic table (and / or an ionic compound composed of ions (cations) of said metal and anions), and optionally further comprises other components to exhibit excellent ionic conductivity.

[0163] (All-solid-state secondary battery)

[0164] The all-solid-state secondary battery of the present invention comprises the solid electrolyte-containing layer of the present invention described above. Here, the all-solid-state secondary battery of the present invention comprises, for example, a positive electrode, a solid electrolyte layer, and a negative electrode, and at least one of the positive electrode composite layer of the positive electrode, the negative electrode composite layer of the negative electrode, and the solid electrolyte layer is the solid electrolyte-containing layer of the present invention. That is, the all-solid-state secondary battery of the present invention comprises a positive electrode having a positive electrode composite layer formed using the all-solid-state secondary battery positive electrode slurry composition as the all-solid-state secondary battery slurry composition of the present invention, a negative electrode having a negative electrode composite layer formed using the all-solid-state secondary battery negative electrode slurry composition as the all-solid-state secondary battery slurry composition of the present invention, and at least one solid electrolyte layer formed using the all-solid-state secondary battery electrolyte layer slurry composition as the all-solid-state secondary battery slurry composition of the present invention.

[0165] Furthermore, since the all-solid-state secondary battery of the present invention is equipped with the solid electrolyte-containing layer of the present invention, cell characteristics such as output characteristics and cycle characteristics are excellent.

[0166] Here, as an electrode for a solid-state secondary battery having an electrode composite layer that does not correspond to the solid electrolyte-containing layer of the present invention, which can be used in the solid-state secondary battery of the present invention, any electrode for a solid-state secondary battery may be used, provided that it has an electrode composite layer that does not correspond to the solid electrolyte-containing layer of the present invention.

[0167] In addition, any solid electrolyte layer that does not correspond to the solid electrolyte-containing layer of the present invention, which can be used in the all-solid-state secondary battery of the present invention, is not particularly limited and, for example, any solid electrolyte layer such as the solid electrolyte layer described in Japanese Patent Publication No. 2012-243476, Japanese Patent Publication No. 2013-143299, and Japanese Patent Publication No. 2016-143614, etc. may be used.

[0168] In addition, the all-solid-state secondary battery of the present invention can be obtained by stacking a positive electrode and a negative electrode such that the positive electrode composite layer of the positive electrode and the negative electrode composite layer of the negative electrode face each other with a solid electrolyte layer interposed therebetween, and then obtaining a laminated body by applying pressure as desired, and then placing it in a battery container and sealing it, either in that state or by winding or folding it according to the battery shape. Meanwhile, if necessary, an overcurrent protection element such as expanded metal, a fuse, or a PTC element, or a lead plate may be placed in the battery container to prevent pressure rise inside the battery and overcharging / discharging. The shape of the battery may be any of the following: coin type, button type, sheet type, cylindrical type, prismatic type, or flat type.

[0169] [Example]

[0170] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. Meanwhile, in the following description, "%" and "parts" indicating amounts are based on mass unless otherwise specified.

[0171] In addition, in the examples and comparative examples, the composition of the polymer and the amount insoluble in the solvent, the content of metal components (metal ions of groups 1 and 2 and other metal components) in the binder composition, the dispersibility and storage stability of the slurry composition, the adhesion of the positive electrode composite layer, the ionic conductivity of the solid electrolyte layer, and the output characteristics of the all-solid-state secondary battery were measured or evaluated by the following methods.

[0172] <Creation>

[0173] 100 g of a binder composition containing a polymer was coagulated with 1 L of methanol and then vacuum dried at 60°C for 12 hours. The obtained dry polymer 1 Analysis was performed using H-NMR. Based on the obtained analysis values, the content ratio (mass%) of each monomer unit and structural unit included in the polymer was calculated.

[0174] <Insoluble amount in solvent>

[0175] An aqueous dispersion of the polymer was dried under an environment of 50% humidity and 23°C to 25°C to produce a film with a thickness of 3 ± 0.3 mm. Subsequently, the produced film was cut into 5 mm squares to prepare film pieces. Approximately 1 g of these film pieces was precisely weighed, and the weight of the precisely weighed film piece was designated as W0. Then, the precisely weighed film piece was immersed in 100 g of the solvent of the binder composition (temperature 25°C) for 24 hours. After immersion for 24 hours, the film piece was withdrawn from the solvent, and the withdrawn film piece was vacuum dried at 105°C for 3 hours, and its weight (weight of insoluble matter) W1 was precisely weighed. Then, the amount of insoluble matter (%) relative to the solvent was calculated according to the following formula.

[0176] Insoluble amount in solvent (%) = W1 / W0 × 100

[0177] <Metal Content>

[0178] About 1 g of the binder composition was heated in an electric furnace at 550°C for about 3 hours and incinerated. Afterward, about 5 mL of concentrated sulfuric acid was added to the incinerated binder composition to dissolve it, and about 5 mL of concentrated nitric acid was slowly added to perform wet decomposition. After decomposition, the acid was concentrated and diluted to 10 mL with ultrapure water, and the metal ion concentration in the binder composition was measured using an ICP-AES device (manufactured by SII Nanotechnologies, model number "SPS-5100"). Based on the obtained metal ion concentration values, the content of Group 1 and 2 metal ions and the content of palladium, ruthenium, and rhodium in the polymer were calculated.

[0179] Dispersibility

[0180] The viscosity of the slurry composition for the solid electrolyte layer was measured using a Brookfield Type B viscometer at 60 rpm (25°C) and evaluated according to the following criteria. A lower viscosity of the slurry composition indicates that the solid electrolyte contained in the slurry composition is well dispersed.

[0181] A: Viscosity less than 4000 mPa·s

[0182] B: Viscosity of 4000 mPa·s or more and less than 5500 mPa·s

[0183] C: Viscosity of 5500 mPa·s or more and less than 8000 mPa·s

[0184] D: Viscosity of 8000 mPa·s or higher or not dispersed (no flow)

[0185] <Preservation Stability>

[0186] A portion of the slurry composition immediately after preparation (slurry composition for the solid electrolyte layer, slurry composition for the positive electrode composite layer) was sampled. The solvent was removed from the sampled slurry composition by drying it on a hot plate at 130°C for 1 hour, and the initial solid content concentration of the slurry composition was measured.

[0187] Next, the slurry composition was stored in a sealed state at 25°C. The top of the stored slurry composition was sampled every 1 day (24 hours) until the 6th day, and the solid content concentration was measured using the same method as above. Then, the storage days at which the solid content concentration decreased by 1.0% or more from the initial concentration were recorded and evaluated according to the following criteria. The longer the said period, the more difficult it is for the solid content in the slurry composition to settle, indicating that the slurry composition has excellent storage stability.

[0188] A: Even at the point where the storage period is 6 days, no decrease in solid content concentration is observed.

[0189] B: Confirm a decrease in solid content concentration after a storage period of 4 or 5 days.

[0190] C: Confirm a decrease in solid content concentration after a storage period of 2 or 3 days.

[0191] D: Confirmed a decrease in solid content concentration at a preservation period of 1 day.

[0192] <Adhesion>

[0193] The positive electrode was cut into a rectangle measuring 1.0 cm in width × 10 cm in length to serve as a test specimen. Cellophane tape (as specified in JIS Z1522) was attached to the surface of the positive electrode composite layer of the test specimen, and the stress was measured when the cellophane tape was peeled off from one end of the test specimen in a 180° direction at a speed of 50 mm / min. A total of three measurements were taken, and the average value was calculated and set as the peel strength (N / m), which was evaluated according to the following criteria. A higher peel strength indicates that the positive electrode composite layer has superior adhesion and is firmly adhered to the current collector.

[0194] A+: Peel strength 4 N / m or higher

[0195] A: Peel strength is 3 N / m or more and less than 4 N / m

[0196] B: Peel strength 2 N / m or more and less than 3 N / m

[0197] C: Peel strength 1 N / m or more and less than 2 N / m

[0198] D: Peel strength less than 1 N / m

[0199] Ion Conductivity

[0200] First, a slurry composition for a solid electrolyte layer was dried on a hot plate at 130°C inside a glove box (moisture content 1 ppm or less), and the resulting powder was molded into a cylinder with a diameter of 10 mm and a thickness of 1 mm to serve as a measurement sample. For this measurement sample, the lithium ion conductivity (25°C) was measured using the AC impedance method. Meanwhile, a frequency response analyzer (manufactured by Solartron Analytical, product name "Solartron 1260" (registered trademark)) was used for the measurement, and the measurement conditions were set to an applied voltage of 10 mV and a measurement frequency range of 0.01 MHz to 1 MHz. The obtained lithium ion conductivity was designated as S0.

[0201] Separately, the slurry composition was dried on a hot plate at 130°C in a dry room (moisture content 127 ppm or less, dew point equivalent to -40°C), and the obtained powder was molded into a cylinder with a diameter of 10 mm and a thickness of 0.5 mm to be used as a measurement sample. For this measurement sample, the lithium ion conductivity (25°C) was measured in the same manner as S0 above. The obtained lithium ion conductivity was designated as S1.

[0202] Then, the conductivity retention rate = S1 / S0 × 100(%) was calculated and evaluated according to the following criteria. The higher the conductivity retention rate, the more the deterioration of the solid electrolyte due to moisture is suppressed, indicating that the solid electrolyte layer prepared using the slurry composition can exhibit excellent ion conductivity.

[0203] A: Conductivity retention rate of 90% or higher

[0204] B: Conductivity retention rate is 80% or higher and less than 90%

[0205] C: Conductivity retention rate is 50% or more and less than 80%

[0206] D: Conductivity retention rate is 30% or more and less than 50%

[0207] E: Conductivity retention rate less than 30%

[0208] <Output Characteristics>

[0209] A 3-cell all-solid-state secondary battery was charged to 4.2 V using the constant current method at 0.1 C, and then discharged to 3.0 V at 0.1 C to determine the 0.1 C discharge capacity. Subsequently, the battery was charged to 4.2 V at 0.1 C, and then discharged to 3.0 V at 2 C to determine the 2 C discharge capacity. The average value of the 0.1 C discharge capacity of the 3 cells was designated as discharge capacity a, and the average value of the 2 C discharge capacity of the 3 cells was designated as discharge capacity b. The ratio of discharge capacity b to discharge capacity a (capacity ratio) = discharge capacity b / discharge capacity a × 100 (%) was calculated and evaluated according to the following criteria. A higher capacity ratio indicates that the all-solid-state secondary battery has superior output characteristics.

[0210] A+: Volume ratio of 85% or more

[0211] A: Volume ratio of 80% or more and less than 85%

[0212] B: Volume ratio of 70% or more and less than 80%

[0213] C: Volume ratio is 60% or more and less than 70%

[0214] D: Volume ratio less than 60%

[0215] (Example 1)

[0216] <Preparation of Binder Composition>

[0217] 100 parts of ion-exchanged water and 0.2 parts of sodium lauryl sulfate as an emulsifier were added to a 1 L flask equipped with a septum and a stirrer, the gas phase was replaced with nitrogen gas, and after raising the temperature to 60°C, 0.25 parts of ammonium persulfate as a polymerization initiator were dissolved in 20.0 parts of ion-exchanged water and added.

[0218] Meanwhile, in another container, a monomer composition was obtained by mixing 40 parts of ion-exchanged water, 1.0 parts of sodium lauryl sulfate as an emulsifier, and 6 parts of acrylonitrile, 69 parts of butyl acrylate, and 25 parts of styrene as monomers. Polymerization was carried out by continuously adding this monomer composition to the above-mentioned 1 L flask equipped with a septum over a period of 3 hours. During the addition, the reaction was carried out at 60°C. After the addition was finished, the reaction was terminated by stirring at 80°C for an additional 3 hours. Using the aqueous dispersion of the obtained polymer, the amount of the polymer insoluble in diisobutyl ketone (solvent) was measured, and it was determined whether the polymer was soluble or sparingly soluble with respect to diisobutyl ketone. The results are shown in Table 1.

[0219] Next, an appropriate amount of sodium hydroxide was added to the aqueous dispersion of the obtained polymer, and an appropriate amount of diisobutyl ketone was added as a solvent to obtain a mixture. Subsequently, vacuum distillation was performed at 80°C to remove water and excess diisobutyl ketone from the mixture, and a binder composition (solid content: 8%) was obtained. Using the obtained binder composition, the composition of the polymer was measured. In addition, the content of metal components in the binder composition was measured. All results are shown in Table 1.

[0220] <Preparation of Slurry Composition for Positive Electrode Combined Layer>

[0221] 70 parts of lithium cobaltate (number average particle size: 11.5 μm) as a positive electrode active material, 25.5 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5 = 70 mol% / 30 mol%, number average particle size: 0.9 μm) as a solid electrolyte, 2.5 parts of acetylene black as a conductive material, and 2 parts of the binder composition obtained as described above (equivalent to solid content) were mixed. Additionally, diisobutyl ketone was added as a solvent to adjust the solid content concentration to 80%, and the mixture was mixed using a planetary mixer for 60 minutes. Subsequently, diisobutyl ketone was added further to adjust the solid content concentration to 70%, and the mixture was mixed for 10 minutes to prepare a slurry composition for the positive electrode composite layer. The storage stability of the obtained slurry composition for the positive electrode composite layer was evaluated. The results are shown in Table 1.

[0222] <Preparation of Slurry Composition for Solid Electrolyte Layer>

[0223] 100 parts of a sulfide glass composed of Li2S and P2S5 as a solid electrolyte (Li2S / P2S5 = 70 mol% / 30 mol%, number average particle size: 0.9 μm) and 2 parts of a binder composition (equivalent to solid content) obtained as described above were mixed, and diisobutyl ketone was added to the resulting mixture to prepare a composition with a solid content concentration of 80%. This composition was mixed at 2000 rpm for 2 minutes using a rotational mixer (product name "Awatori Rentaro (registered trademark) ARE310". The same applies hereinafter). Diisobutyl ketone was added to the resulting mixture to prepare a composition with a solid content concentration of 70%. This composition was mixed at 2000 rpm for 2 minutes using a rotational mixer. Diisobutyl ketone was added to the obtained mixture to prepare a composition with a solid content of 65%. This composition was mixed using a rotational mixer at 2000 rpm for 2 minutes. Diisobutyl ketone was added to the obtained mixture to prepare a composition with a solid content of 60%. This composition was mixed using a rotational mixer at 2000 rpm for 2 minutes. Diisobutyl ketone was added to the obtained mixture to prepare a composition with a solid content of 55%. This composition was mixed using a rotational mixer at 2000 rpm for 2 minutes. Diisobutyl ketone was added to the obtained mixture to prepare a composition with a solid content of 50%. This composition was mixed using a rotational mixer at 2000 rpm for 2 minutes to obtain a slurry composition for a solid electrolyte layer. The dispersibility and storage stability of the obtained slurry composition for the solid electrolyte layer were evaluated. In addition, the ionic conductivity of the solid electrolyte layer was evaluated using the obtained slurry composition for the solid electrolyte layer. All results are shown in Table 1.

[0224] Production of Straight Drama

[0225] The slurry composition for the positive electrode composite layer was applied to the surface of a current collector (aluminum foil, thickness: 20 μm) and dried (120°C, 60 minutes) to form a positive electrode composite layer with a thickness of 50 μm, thereby obtaining a positive electrode. The adhesion of the positive electrode composite layer was evaluated using this positive electrode. The results are shown in Table 1.

[0226] Manufacturing of All-Solid State Secondary Batteries

[0227] 65 parts of graphite (number average particle size: 20 μm) as a negative electrode active material, 31.5 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5 = 70 mol% / 30 mol%, number average particle size: 0.9 μm) as solid electrolyte particles, 1.5 parts of acetylene black as a conductive material, and 2 parts of the binder composition (equivalent to solid content) obtained as described above were mixed, and diisobutyl ketone was added as a solvent to adjust the solid content concentration to 65%, and then mixed with a planetary mixer for 60 minutes. After that, diisobutyl ketone was further added to adjust the solid content concentration to 60%, and then mixed with a planetary mixer to prepare a slurry composition for a negative electrode composite layer. Then, the slurry composition for the negative electrode composite layer was applied to the surface of the current collector (copper foil, thickness: 15 μm) and dried (120°C, 60 minutes) to form a negative electrode composite layer with a thickness of 60 μm, thereby obtaining a negative electrode.

[0228] Next, the slurry composition for the solid electrolyte layer was applied to the surface of the positive electrode composite layer of the above positive electrode and dried (120°C, 60 minutes) to form a solid electrolyte layer with a thickness of 150 μm, thereby obtaining a positive electrode with a solid electrolyte layer formed.

[0229] The positive electrode forming the solid electrolyte layer and the negative electrode were laminated so that the solid electrolyte layer of the positive electrode forming the solid electrolyte layer and the negative electrode composite layer of the negative electrode were in contact, and pressed to obtain an all-solid-state secondary battery. The thickness of the solid electrolyte layer of the all-solid-state secondary battery after pressing was 100 μm. The output characteristics of this all-solid-state secondary battery were evaluated. The results are shown in Table 1.

[0230] (Example 2)

[0231] Except for using a binder composition prepared as described below, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.

[0232] <Preparation of Binder Composition>

[0233] 100 parts of ion-exchanged water and 0.2 parts of sodium lauryl sulfate as an emulsifier were added to a 1 L flask equipped with a septum and a stirrer, the gas phase was replaced with nitrogen gas, and after raising the temperature to 60°C, 0.25 parts of ammonium persulfate as a polymerization initiator were dissolved in 20.0 parts of ion-exchanged water and added.

[0234] Meanwhile, in another container, a monomer composition was obtained by mixing 40 parts of ion-exchanged water, 1.0 parts of sodium lauryl sulfate as an emulsifier, and 7 parts of acrylonitrile, 50 parts of butyl acrylate, 23 parts of ethyl acrylate, and 20 parts of phenoxyethyl acrylate as monomers. Polymerization was carried out by continuously adding this monomer composition to the above-mentioned 1 L flask equipped with a septum over a period of 3 hours. During the addition, the reaction was carried out at 60°C. After the addition was finished, the reaction was terminated by stirring at 80°C for an additional 3 hours. Using the aqueous dispersion of the obtained polymer, the amount of the polymer insoluble in diisobutyl ketone (solvent) was measured, and it was determined whether the polymer was soluble or sparingly soluble with respect to diisobutyl ketone. The results are shown in Table 1.

[0235] Next, an appropriate amount of sodium hydroxide was added to the aqueous dispersion of the obtained polymer, and an appropriate amount of diisobutyl ketone was added as a solvent to obtain a mixture. Subsequently, vacuum distillation was performed at 80°C to remove water and excess diisobutyl ketone from the mixture, and a binder composition (solid content: 8%) was obtained. Using the obtained binder composition, the composition of the polymer was measured. In addition, the content of metal components in the binder composition was measured. All results are shown in Table 1.

[0236] (Examples 3, 4)

[0237] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that xylene (Example 3) and butyl butyrate (Example 4) were used instead of diisobutyl ketone as solvents when preparing the binder composition and the slurry composition, respectively, and various evaluations were performed. The results are shown in Table 1.

[0238] (Example 5)

[0239] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that the amount of sodium hydroxide added to the aqueous dispersion of the polymer was increased when preparing the binder composition, and various evaluations were performed. The results are shown in Table 1.

[0240] (Example 6)

[0241] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that polyoxyethylene lauryl ether was used instead of sodium lauryl sulfate as an emulsifier when preparing the binder composition, and the amount of sodium hydroxide added to the aqueous dispersion of the polymer was reduced, and various evaluations were performed. The results are shown in Table 1.

[0242] (Examples 7, 8)

[0243] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 6, except that 7 parts of acrylonitrile, 50 parts of butyl acrylate, 23 parts of ethyl acrylate, and 20 parts of phenoxyethyl acrylate were used as monomers when preparing the binder composition, and lithium hydroxide (Example 7) and magnesium hydroxide (Example 8) were each added in appropriate amounts to the aqueous dispersion of the polymer instead of sodium hydroxide, and various evaluations were performed. The results are shown in Table 1.

[0244] (Example 9)

[0245] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that 32 parts of acrylonitrile, 58 parts of butyl acrylate, and 10 parts of styrene were used as monomers when preparing the binder composition, and various evaluations were performed. The results are shown in Table 1.

[0246] (Example 10)

[0247] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that 2 parts of acrylonitrile, 80 parts of butyl acrylate, and 18 parts of styrene were used as monomers when preparing the binder composition, and various evaluations were performed. The results are shown in Table 2.

[0248] (Example 11)

[0249] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that 6 parts of acrylonitrile, 88 parts of butyl acrylate, and 6 parts of styrene were used as monomers when preparing the binder composition, and various evaluations were performed. The results are shown in Table 2.

[0250] (Example 12)

[0251] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that 35 parts of acrylonitrile, 25 parts of butyl acrylate, and 40 parts of styrene were used as monomers when preparing the binder composition, and various evaluations were performed. The results are shown in Table 2.

[0252] (Example 13)

[0253] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that 15 parts of acrylonitrile, 80 parts of butyl acrylate, and 5 parts of styrene were used as monomers when preparing the binder composition, and various evaluations were performed. The results are shown in Table 2.

[0254] (Example 14)

[0255] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that 6 parts of acrylonitrile, 54 parts of butyl acrylate, and 40 parts of styrene were used as monomers when preparing the binder composition, and various evaluations were performed. The results are shown in Table 2.

[0256] (Example 15)

[0257] Except for using a binder composition prepared as described below, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2.

[0258] <Preparation of Binder Composition>

[0259] 2 parts of potassium oleate as an emulsifier, 0.1 parts of potassium phosphate as a stabilizer, and 150 parts of water were added to a reactor. Additionally, 20 parts of acrylonitrile, 43 parts of 1,3-butadiene, 33 parts of butyl acrylate, and 14 parts of styrene were added as monomers, and 0.31 parts of t-dodecyl mercaptan were added as a molecular weight adjuster. Emulsion polymerization was initiated at 10°C in the presence of 0.015 parts of ferrous sulfate as an activator and 0.05 parts of paramethan hydroperoxide as a polymerization initiator. When the polymerization conversion rate reached 85%, 0.2 parts of hydroxylamine sulfate were added to 100 parts of monomers to stop the polymerization.

[0260] After stopping the polymerization, the unreacted monomer was recovered by steam distillation at 70°C under reduced pressure after heating, and then 2 parts of alkylated phenol were added as an anti-aging agent to obtain a copolymer latex.

[0261] 400 mL of the obtained copolymer latex (total solids: 48 g) was placed into a 1-liter autoclave equipped with a stirrer, and nitrogen gas was flowed for 10 minutes to remove dissolved oxygen from the copolymer solution. Subsequently, 50 mg of palladium acetate was dissolved in 180 mL of water to which 4 molar nitric acid relative to Pd was added as a hydrogenation reaction catalyst, and the mixture was added. After purging the system with hydrogen gas twice, the contents of the autoclave were heated to 50°C under hydrogen gas pressure of up to 3 MPa, and the hydrogenation reaction was carried out for 6 hours.

[0262] The contents were returned to room temperature, the system was conditioned to a nitrogen atmosphere, and then concentrated using an evaporator until the solid content concentration reached 40% to obtain an aqueous dispersion of the polymer (hydrogenated nitrile rubber). Using the obtained aqueous dispersion of the polymer, the amount of the polymer insoluble in diisobutyl ketone (solvent) was measured, and it was determined whether the polymer was soluble or insoluble in diisobutyl ketone. The results are shown in Table 2.

[0263] Next, an appropriate amount of potassium hydroxide was added to the aqueous dispersion of the obtained polymer, and an appropriate amount of diisobutyl ketone was added as a solvent to obtain a mixture. Subsequently, vacuum distillation was performed at 80°C to remove water and excess diisobutyl ketone from the mixture, and a binder composition (solid content: 8%) was obtained. Using the obtained binder composition, the composition of the polymer was measured. In addition, the content of metal components in the binder composition was measured. All results are shown in Table 2.

[0264] (Example 16)

[0265] Except for using a binder composition prepared as described below, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2.

[0266] <Preparation of Binder Composition>

[0267] <<Preparation of a first binder composition comprising a first polymer>>

[0268] A first binder composition containing a first polymer was prepared in the same manner as the binder composition of Example 1, except that 7 parts of acrylonitrile, 50 parts of butyl acrylate, 23 parts of ethyl acrylate, and 20 parts of phenoxyethyl acrylate were used as monomers. Furthermore, in the same manner as in Example 1, whether the first polymer was soluble or insoluble, and the composition of the first polymer were determined, and furthermore, the content of the metal component in the binder composition was measured. The results are shown in Table 2.

[0269] <<Preparation of a second binder composition containing a second polymer>>

[0270] A second binder composition containing a second polymer was prepared in the same manner as the binder composition of Example 1, except that 10 parts of acrylonitrile, 69.5 parts of butyl acrylate, 20 parts of styrene, and 0.5 parts of allyl methacrylate were used as monomers. In addition, in the same manner as in Example 1, whether the second polymer was soluble or insoluble and the composition of the second polymer were determined, and furthermore, the content of the metal component in the binder composition was measured. The results are shown in Table 2.

[0271] <<Mixing of the first binder composition and the second binder composition>>

[0272] A binder composition was prepared by mixing the first binder composition described above and the second binder composition described above such that the solid content equivalent amount of the first polymer and the second polymer is 1:1 (mass ratio).

[0273] (Example 17)

[0274] When preparing the binder composition, 7 parts of acrylonitrile, 50 parts of butyl acrylate, 23 parts of ethyl acrylate, and 20 parts of phenoxyethyl acrylate are used as monomers, and when preparing the slurry composition (slurry composition for a solid electrolyte layer, slurry composition for a positive electrode composite layer), an oxide-based inorganic solid electrolyte (Li7La3Zr2O2) is used instead of sulfide glass. 12 Except for using (number average particle size: 1.2 μm), a binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2.

[0275] (Example 18)

[0276] A slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, except that a second binder composition containing a second polymer prepared in the same manner as in Example 16 was used as the binder composition, and various evaluations were performed. The results are shown in Table 2.

[0277] (Example 19)

[0278] Except for using a binder composition prepared as described below, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, a positive electrode, and an all-solid-state secondary battery were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 3.

[0279] <Preparation of Binder Composition>

[0280] In the reactor, 180 parts of ion-exchanged water, 25 parts of an aqueous solution of sodium dodecylbenzenesulfonate (concentration 10%) as an emulsifier, 20 parts of acrylonitrile and 25 parts of butyl acrylate as monomers, and 0.3 parts of t-dodecyl mercaptan as a molecular weight adjuster were added in this order. Subsequently, after purging the gas inside the reactor with nitrogen three times, 55 parts of 1,3-butadiene as a monomer were added. In the reactor maintained at 10°C, 0.1 parts of cumene hydroperoxide and 0.1 parts of ferrous sulfate as polymerization initiators were added to start the polymerization reaction, and the polymerization reaction was carried out while stirring. When the polymerization conversion rate reached 90%, 0.2 parts of hydroxylamine sulfate were added to 100 parts of the monomer to stop the polymerization. Next, the residual monomer was removed under reduced pressure at a water temperature of 80°C, and a particulate aqueous dispersion of the polymer precursor (copolymer latex) was obtained.

[0281] 400 mL of the obtained copolymer latex (total solids: 48 g) was placed into a 1-liter autoclave equipped with a stirrer, and nitrogen gas was flowed for 10 minutes to remove dissolved oxygen from the copolymer latex. Subsequently, 50 mg of palladium acetate was dissolved in 180 mL of water to which 4 molar nitric acid relative to Pd was added as a hydrogenation reaction catalyst, and the mixture was added. After purging the system with hydrogen gas twice, the contents of the autoclave were heated to 50°C under hydrogen gas pressure of up to 3 MPa, and the hydrogenation reaction was carried out for 6 hours.

[0282] In addition, 50 g of the obtained polymer was placed in a cellulose tube for dialysis with a pore size of 5 nm, sealed, and then immersed in a container containing ion-exchanged water. The residual palladium was removed by dialysis for 48 hours while passing surrounding ion-exchanged water through it.

[0283] Next, appropriate amounts of sodium hydroxide, a ruthenium organic complex, and a rhodium organic complex were added to the aqueous dispersion of the obtained polymer, and an appropriate amount of diisobutyl ketone was added as a solvent to obtain a mixture. Subsequently, vacuum distillation was performed at 80°C to remove water and excess diisobutyl ketone from the mixture, and a binder composition (solid content: 8%) was obtained. Using the obtained binder composition, the composition of the polymer was measured. In addition, the content of metal components in the binder composition was measured. All results are shown in Table 3.

[0284] (Comparative Example 1)

[0285] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, and a positive electrode were prepared in the same manner as in Example 1, except that polyoxyethylene lauryl ether was used instead of sodium lauryl sulfate as an emulsifier when preparing the binder composition, and sodium hydroxide was not added to the aqueous dispersion of the polymer, and various evaluations were performed. The results are shown in Table 3. Meanwhile, the binder composition did not contain metal ions of Group 1 or 2 (less than 5 mass ppm relative to the polymer).

[0286] (Comparative Example 2)

[0287] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, and a positive electrode were prepared in the same manner as in Example 5, except that the amount of sodium hydroxide added was further increased when preparing the binder composition, and various evaluations were performed. The results are shown in Table 3.

[0288] (Comparative Examples 3~5)

[0289] A binder composition, a slurry composition for a positive electrode composite layer, a slurry composition for a solid electrolyte layer, and a positive electrode were prepared in the same manner as in Example 1, except that 4-heptane (Comparative Example 3), methyl isobutyl ketone (Comparative Example 4), and ethyl acetate (Comparative Example 5) were used, respectively, instead of diisobutyl ketone when preparing the binder composition and the slurry composition, and various evaluations were performed. The results are shown in Table 3.

[0290] Meanwhile, among Tables 1 to 3 shown below,

[0291] "Vinyl cyanide" represents a vinyl cyanide monomer unit, and

[0292] "(Met)acrylic acid ester (ring-free)" represents a (meth)acrylic acid ester monomer unit that does not have an aromatic hydrocarbon ring, and

[0293] "Aromatic" refers to an aromatic monomer unit, and

[0294] "AN" represents an acrylonitrile unit, and

[0295] "BA" represents a butyl acrylate unit,

[0296] "EA" represents an ethyl acrylate unit, and

[0297] "ST" represents a styrene unit, and

[0298] "PEA" represents a phenoxyethyl acrylate unit, and

[0299] "H-BD" represents a 1,3-butadiene hydride unit, and

[0300] "AMA" represents the allyl methacrylate unit,

[0301] "This" indicates usability,

[0302] "Nan" indicates insoluble properties,

[0303] "DIK" represents diisobutyl ketone,

[0304] "XY" represents xylene,

[0305] "HB" represents butyl butyrate,

[0306] "HE" represents 4-heptanone, and

[0307] "MBK" represents methylisobutylketone,

[0308] "EAc" represents ethyl acetate,

[0309] "Sulpide" refers to a sulfide-based solid electrolyte,

[0310] "Oxide" refers to an oxide-based solid electrolyte,

[0311] "Na" represents the sodium ion,

[0312] "Li" represents lithium ions,

[0313] "Mg" represents the magnesium ion,

[0314] "K" represents potassium ions,

[0315] "Pd" represents palladium,

[0316] "Ru" represents ruthenium,

[0317] "Rh" represents rhodium,

[0318] "The number of C" represents the number of carbon atoms.

[0319]

[0320]

[0321]

[0322] From Tables 1 to 3, it can be seen that according to the binder compositions of Examples 1 to 19, it is possible to prepare a slurry composition having excellent dispersibility and storage stability, while simultaneously forming a solid electrolyte layer having excellent ion conductivity. In addition, in Examples 1 to 19, it can be seen that the adhesion of the positive electrode composite layer is good, and the all-solid-state secondary battery can exhibit excellent output characteristics.

[0323] Meanwhile, from Table 3, it can be seen that in Comparative Examples 1 and 2, which used binder compositions in which the content of metal ions of Group 1 and 2 was outside the specified range, the dispersibility and storage stability of the slurry composition, the ionic conductivity of the solid electrolyte layer, the adhesion of the positive electrode composite layer, and the output characteristics of the all-solid-state secondary battery were reduced.

[0324] In addition, from Table 3, it can be seen that in Comparative Examples 3 to 5, which used binder compositions containing only organic solvents having 7 or fewer carbon atoms as solvents, the dispersibility and storage stability of the slurry composition, the ionic conductivity of the solid electrolyte layer, the adhesion of the positive electrode composite layer, and the output characteristics of the all-solid-state secondary battery are reduced.

[0325] [Industrial Applicability]

[0326] According to the present invention, it is possible to prepare a slurry composition for an all-solid-state secondary battery having excellent dispersibility and storage stability, and at the same time, provide a binder composition for an all-solid-state secondary battery that can exhibit excellent ion conductivity in a solid electrolyte-containing layer.

[0327] In addition, according to the present invention, a slurry composition for an all-solid-state secondary battery can be provided that is capable of forming a solid electrolyte-containing layer with excellent dispersibility and storage stability, while also having excellent ion conductivity.

[0328] In addition, according to the present invention, a solid electrolyte containing layer having excellent ion conductivity and an all-solid-state secondary battery having said solid electrolyte containing layer can be provided.

Claims

Claim 1 A binder composition for an all-solid-state secondary battery comprising a polymer, ions of a metal belonging to Group 1 or Group 2 of the periodic table, and a solvent, wherein the solvent comprises an organic solvent having 8 or more carbon atoms, and the polymer comprises vinyl cyanide monomer units in an amount of 2 mass% or more and 7 mass% or less, (meth)acrylic acid ester monomer units not having an aromatic hydrocarbon ring in an amount of 35 mass% or more and 73 mass% or less, and aromatic monomer units in an amount of 3 mass% or more and 35 mass% or less, and the content of the metal ions is 5 mass ppm or more and 5,000 mass ppm or less relative to the polymer. Claim 2 A binder composition for an all-solid-state secondary battery according to claim 1, wherein the organic solvent having 8 or more carbon atoms has at least one selected from the group consisting of an aromatic hydrocarbon ring, a non-aromatic hydrocarbon group, and a carbonyl group. Claim 3 A binder composition for an all-solid-state secondary battery according to claim 1, wherein the aromatic monomer unit comprises a (meth)acrylic acid ester monomer unit having an aromatic hydrocarbon ring. Claim 4 A slurry composition for an all-solid-state secondary battery comprising a solid electrolyte and a binder composition for an all-solid-state secondary battery described in claim 1. Claim 5 A slurry composition for an all-solid-state secondary battery according to claim 4, wherein the solid electrolyte comprises at least one of a sulfide-based inorganic solid electrolyte and an oxide-based inorganic solid electrolyte. Claim 6 A solid electrolyte-containing layer formed using the all-solid-state secondary battery slurry composition described in claim 4 or 5. Claim 7 All-solid-state secondary battery having a solid electrolyte-containing layer as described in claim 6. Claim 8 delete Claim 9 delete Claim 10 delete Claim 11 delete

Citation Information

Patent Citations

  • Binder composition for all-solid secondary battery, slurry composition for all-solid secondary battery, functional layer for all-solid secondary battery, and all-solid secondary battery

    WO2019116964A1